The Use of a Diode Laser for Removal of Microorganisms from the Surfaces of Zirconia and Porcelain Applied to Superstructure Dental Implants - Anna Wawrzyk; Michał Łobacz; Agnieszka Adamczuk; Weronika Sofińska-Chmiel; Sławomir Wilczyński; Mansur Rahnama (Microorganisms, 2021)
The aim of this paper was to study the effectiveness of a diode laser (LD) for removal of microorganisms isolated from porcelain and zirconia crown surfaces used in implantoprosthetics in order to minimize infections around dental implants. In order to optimize biocidal efficacy of the process (at the same time, avoiding increasing the surface roughness during decontamination) the effects of diode laser doses were investigated. The irradiation was performed with a diode laser at the wavelength of λ = 810 nm in three variants with a different number of repetitions (1 × 15 s, 2 × 15 s, 3 × 15 s). The quantitative microbial contamination of the surface of teeth, porcelain and zirconia crowns assessment was made using the culture-dependent method. The identification of microorganisms took place using the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and next-generation sequencing (NGS) methods. The studies of the surface morphology and roughness were carried out by means of the optical profilometry, scanning electron microscopy (SEM) and optical microscopy with the C1 confocal attachment. The most important conclusion from the research is the fact that the laser operation, regardless of the exposure time, effectively eliminates the microorganisms from the surfaces used for dental implant rebuilding and does not have a destructive effect on the tested material.